(3JQHjI GdeDefjf aj JChjd OYGFe GdGSdGes - (3GdbGVj GdfYeGf Hf Mjhf , CHh Mfjag GdfYeGf Hf eMeO Hf efUhQ Hf CMeO Hf Mjhf GdeUQj,J (B363 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdYGde HeG cGf hHeG jchf hHjeG de jcf EPG cGf cja jchf hHYO GdeLdS GdChd ai Gdbhd ai JChjd GdUdGI heG LGA ef MOhO gG Ydi GdJeGe s
(3BNQgG (B:s
(3hHYO gPG SCdJ ai Mb ehdGfG CWGd Gddg YeQI hHYOg bQCJ aVjdI QLH hUheg hUdhGJg hHjGf djdI GdeYQGL s
(3GdfSNI HgG MhGTs
(3QJH Ydi (B12 (3LRAs
(3hcd LRA (B10 (3eLGdSs
(3GdehLhO eLdOjf s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
Keywords: (3eJaQbGJs